Sukuk, Systemic Risk, and Economic Growth in Emerging Markets - Aisyah Putri Wibowo, Nabila; Daryono (Journal International Economic Sharia, 2025)
Objective: The focus of this paper is to examine the effect that the development of the sukuk market has on sustainable economic growth. It also looks at how financial system stability can act as a mediator in developing nations.Methods: Longitudinal panel data analysis will be conducted using advanced econometric tools, focusing on hypothesised relationships such as mediation with a bootstrapping approach.Results: Sukuk development significantly stimulates sustainable economic growth, with Green Sukuk having the most significant impact. Financial system stability is found to be an important mediator between the surplus/nexus and the solidarity/country mechanisms, mediating almost fifty percent of the overall effects. The findings suggest that risk-sharing Sukuk arrangements can significantly enhance financial resilience and sustainable development prospects.Novelty: This study is the first to derive financial fragility as a mediating variable and examine how Islamic capital markets transmit monetary policy to sustainable development. It also explores different Sukuk types within a coherent theoretical framework.Research Implication: The results provide strategic direction for policymakers and financial institutions intending to utilize Islamic finance as a platform for development with sustainable goals, focusing on the necessity of incorporating financial stability concerns into their strategies.